Population and Behavior of Proboscis Monkey (Nasalis larvatus) in Samboja Koala, Earl Kalimantan - Hadi S Alikodra (Department of Forest Resources Conservation and Ecotourism - IPB University, 1997)
The proboscis monkey (Nasalis lavartus ) is a member of sub-family Colobinae, and a sexually species, endemic to Kalimantan. The habitat of the monkey in confined mainly to mangrove, riverine forest and peat swamp forest. Habitat degradation in major factor which disturbe the population of this species. a Habitat, Koala Samboja has undergone a lot of disturbances, especially bby various activities of the people who are inhabiting this area. The aim of the study was to know some ecological parameters, habitat, population and behavior of the proboscis monkey. The study was done at River of Koala, Samboja, East Kalimantan.